The READABILITY LEVEL OF READING TEXTS IN THE ENGLISH TEXT BOOK ENTITLED “BAHASA DAN SASTRA INGGRIS SMA/MA” FOR GRADE X SEMESTER 1 - Penu, Stella Eliza; Liando, Nihta; Rettob, Aloysius (KOMPETENSI, 2022)
The cause of this observe is to recognise the clarity degree of studying texts in English language textbooks utilized by trainer. This studies make use of quantitative technique to investigate the information. Thirteen studying texts are decided on as studies population. All of decided on texts are analyzed the use of Flesch Reading Ease method. In this studies, the researchers locate clarity of studying texts with inside the “Bahasa dan Sastra Inggris“ aren’t appropriate for 10th grade collage students of excessive college. Based at the end result of Flesch studying ease method, from 13 studying texts, 5 (38.4%) studying texts are too Difficult for 10th grade college students, 2 (15,3%) studying texts are too Standard for 10th college students, three ( 23.0%) studying textual content are too pretty clean for 10th grade and one ( 07.6%) studying textual content are too very clean for 10th college students. They are most effective studying texts (15.3%) appropriate for 10th grade college students.